2012
DOI: 10.1111/sms.12012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation is associated with elite athletic status in the Polish population

Abstract: There is mounting evidence that genetic factors located in mitochondrial and nuclear genomes influence sport performance. Certain mitochondrial haplogroups and polymorphisms were associated with the status of elite athlete, especially in endurance performance. The aim of our study was to assess whether selected mitochondrial DNA (mtDNA) and nuclear DNA variants are associated with elite athlete performance in a group of 395 elite Polish athletes (213 endurance athletes and 182 power athletes) and 413 sedentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
(39 reference statements)
2
24
1
Order By: Relevance
“…In addition, in four case-control studies, significantly lower frequency of 482Ser allele in Spanish (n ¼ 104), Russian (n ¼ 579), Israeli (n ¼ 74), and Polish (n ¼ 92) elite endurance-oriented athletes has been reported [30,133,148,149]. However, while Maruszak et al [116] and He et al [150] have not replicated the same results in 213 Polish and 235 Chinese endurance athletes, respectively, Tural et al [136] have shown an opposite association; that is, 60 Turkish endurance athletes had significantly lower frequency of the Gly482 allele than 110 controls. Additionally, He et al [150] in the study of Chinese athletes have revealed the prevalence of the A allele of the functionally relevant rs4697425 A/G polymorphism in 127 female endurance athletes in comparison with controls (but not in 194 male endurance athletes).…”
Section: Ppargc1a Gly482 and Rs4697425 A Allelesmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, in four case-control studies, significantly lower frequency of 482Ser allele in Spanish (n ¼ 104), Russian (n ¼ 579), Israeli (n ¼ 74), and Polish (n ¼ 92) elite endurance-oriented athletes has been reported [30,133,148,149]. However, while Maruszak et al [116] and He et al [150] have not replicated the same results in 213 Polish and 235 Chinese endurance athletes, respectively, Tural et al [136] have shown an opposite association; that is, 60 Turkish endurance athletes had significantly lower frequency of the Gly482 allele than 110 controls. Additionally, He et al [150] in the study of Chinese athletes have revealed the prevalence of the A allele of the functionally relevant rs4697425 A/G polymorphism in 127 female endurance athletes in comparison with controls (but not in 194 male endurance athletes).…”
Section: Ppargc1a Gly482 and Rs4697425 A Allelesmentioning
confidence: 86%
“…In a study of Finnish elite endurance athletes (n ¼ 52), an excess of mtDNA haplogroup H and the absence of haplogroup K and subhaplogroup J2 compared to 1060 controls and 89 sprinters was reported [115]. Maruszak et al [116] have also shown that haplogroup K was less prevalent in 130 male Polish endurance athletes than in 413 controls, while haplogroups H, HV, and m.16080G allele were overrepresented in elite endurance athletes compared with elite power athletes or controls. Haplogroup T was significantly less frequent among 95 Spanish elite endurance athletes in comparison with 250 healthy male population controls [117].…”
Section: Mtdna Markersmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, the European mitochondrial DNA haplogroup HV has been associated with decreased odds of severe sepsis, suggesting that mitochondrial haplotypes could determine survival rates during severe septic shock due to differences in its function (Baudouin et al, 2005; Lorente et al, 2012; Jiménez-Sousa et al, 2015), higher OXPHOS capacity as well as higher ROS and RONS production (Jiménez-Sousa et al, 2015). More specifically, Maruszak et al (2014) reported that Olympic athletes were primarily from the HV haplogroup, which has been associated with a higher VO 2 max in response to exercise coupled to more OXPHOS capacity and thus more aerobic ATP production, whereas a study in healthy male Spanish Caucasians ( n = 81) also demonstrated that the HV haplogroup was associated with higher ROS production and mitochondrial oxidative damage compared to the JT haplogroup (Martinez et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…However, there are a paucity of data on energy substrate partitioning in elite professional endurance athletes (PAs). Studies on elite athletes are of interest because they express a robust muscle mitochondrial reticulum, perhaps due to genetic and epigenetic variations [7][8][9][10][11][12][13], which allows them to be metabolically flexible [5,6]. Therefore, PAs readily switch back and forth between lipid and CHO oxidation (CHOox), depending on energy demand and substrate availability at higher absolute workloads.…”
Section: Introductionmentioning
confidence: 99%